Is the Spiritual Man Pentecostal? Watchman Nee’s Perspective on the Charismatic Experiences - Zhao, Pan (Religions (Basel, Switzerland ), 2023)
Watchman Nee (Ni Tuosheng, 1903–1972), one of the most prominent theologians in Republican China (1911–1949), developed a “spiritual theology” that is concentrated on the work of the Holy Spirit. This theological perspective shares parallels with Pentecostal-Charismatic theology. This paper examines Nee’s attitude toward Pentecostalism and the charismatic experience. First, based on his teaching of the three-stage work of the Holy Spirit, Nee argued that the inner guidance of the Holy Spirit was more important than any external manifestation and that the “baptism of the Holy Spirit” in the Pentecostal-Charismatic movement was not a personal experience that Christians should pursue. Second, in terms of subjective experience, Nee’s trichotomous view of human nature as consisting of spirit, soul, and body suggested that many charismatic experiences originate in the soul and need to be overcome. Third, concerning the spiritual world, Nee regarded as the work of evil spirits those charismatic experiences that occur in irrational and unconscious situations. Nee’s negative stance towards Pentecostalism and the charismatic experience serves as a means of distinguishing his spiritual theology from Pentecostalist-Charismatic movements. Both Nee’s theology and his church practices reveal a strong elitist element, in stark contrast to Pentecostalism.